(untitled) (Academia Journal of Medicine, 2021)
Introduction: Acute kidney injury (AKI) is a complex clinical disorder that is associated with severe morbidity and mortality, which in spite of technological advances in Renal replacement therapy (RRT), continues to be associated with poor outcomes. AKI is a syndrome of sudden loss of kidney’s excretory function, often associated with oliguria, occurring over hours to days seen commonly in hospitalised patients who are critically ill. Subjects and Methods: A prospective and observational study was conducted at Sapthagiri Institute of Medical Sciences & Research Centre from January 2020 to December 2020. Patients with Acute Kidney Injury satisfying inclusion and exclusion criteria, admitted in the medical Intensive care unit (ICU), were selected after obtaining informed consent. Results: The mean age of the population was 64.51 ± 14.29 years. 65% patients were males. Most common age group was older age group (65 to 75 years) for both males and females. In the younger age group (18-44 years) most of them were males. In the elderly age group (85- 100 years) females exceeded males. The mean duration of hospital stay was 10.78 ± 8.39 days and the median duration of hospital stay was 9 days. The mean duration of ICU stay was 6.15 ± 5.31days and the median duration of ICU stay was 4 days. In our study some patients had AKI on day 1 of ICU admission and the others developed AKI later during the course of ICU stay. The median day of ICU admission on which patients presented with AKI in our study was on the day 1. RRT was initiated in majority of the patients (53%) on the 1st day of ICU admission itself. Remaining patients (25.6%) received RRT on day 2 of ICU admission. Only a few patients (21%) received RRT after 2 days. Conclusion: Elderly males are at higher risk for developing AKI. Sepsis with pneumonia is the leading cause of AKI in ICU. Pre-existing Chronic Kidney disease (CKD )has worse renal outcome. Kidney Disease Improving Global outcomes(KDIGO) staging is an independent predictor of ICU mortality, RRT requirement and ventilatory support. In the setting of acute kidney injury, Acute Physiology and Chronic Health Evaluation (APACHE) III is superior to Sequential Organ Failure Assessment (SOFA) and APACHE II for predicting in-hospital mortality. Patients with AKI have 2.33 times more risk of mortality compared to those without AKI. AKI is an independent predictor of mortality in ICU.